In Vitro Antibacterial Activity of Glutathione Against Aeromonas veronii and Its In Vivo Effects on Intestinal Microbiota in Koi Carp ( Cyprinus carpio Var. koi ) - Haoyue Zhang; Jingfeng Sun; Zhuoran Han; Anli Wang (New Zealand Journal of Marine and Freshwater Research, 2026)
Aeromonas veronii is a pathogenic bacterium that threatens freshwater fish, including koi carp. Antibiotics used to control bacterial infections can disrupt the intestinal microbiota and promote antibiotic resistance. This study aimed to evaluate the in vitro antimicrobial activity of glutathione (GSH) against A. veronii and its impact on the intestinal microbiota of koi carp. To this end, we examined bacterial growth, biofilm formation, and motility of A. veronii . We further analyzed the intestinal microbiota composition by 16S rRNA high‐throughput sequencing and assessed disease resistance in koi carp after 7 days of dietary GSH supplementation. The results showed that GSH inhibited A. veronii growth, biofilm formation, and motility, with stronger effects at higher doses. GSH supplementation also significantly altered the intestinal microbiota, reducing potential pathogenic bacteria like Aeromonas and promoting beneficial ones. Moreover, GSH enhanced disease resistance, with treated fish showing lower cumulative mortality compared to controls. However, the GSH doses of 720 mg/kg caused hepatic burden, emphasizing the need for careful dose optimization. These findings highlight the significance of GSH in modulating the intestinal microbiota of fish, a process that may contribute to enhanced disease resistance, and emphasize the importance of optimizing its dosage for safe application in aquaculture.